The evolving role of zoological parks and aquariums in migratory bird conservation. Issue 5 (4th September 2018) - Hutchins, Michael; Marra, Peter P.; Diebold, Ed; Kreger, Michael D.; Sheppard, Christine; Hallager, Sara; Lynch, Colleen
Abstract : As threats to migratory birds in the Western Hemisphere, including North America, intensify and bird populations decline, there is a growing interest among zoo biologists in the conservation and management of these taxa. The purpose of this article is to explore the role that Association of Zoos and Aquariums (AZA)‐accredited zoos and aquariums either are playing or could play in the conservation and management of migratory birds. Topics explored include: (1) Public education and advocacy; (2) Captive breeding and reintroduction; (3) In situ conservation; (4) Tracking and monitoring; (5) Research/technology development; and (6) Sustainability/green practices; and (7) Partnerships. Zoos and aquariums could play an important role in increasing the public's access to understanding migratory birds and the threats they face, ultimately helping to protect these remarkable species.